Foliar mineral content of five shrub species with nutritional potential for small ruminants in semiarid regions in northeastern Mexico - Espinoza, Miguel Chávez; Rodríguez, Humberto González; Silva, Israel Cantú; Correa, Mauricio Cotera; Castillón, Andrés Eduardo Estrada; Barragán, Hugo Bernal; Meza, Marco Vinicio Gómez (Universidade Federal de Santa Maria, 2020)
This study was conducted to determine the monthly composition of the minerals Ca, P, K, Mg, Cu, Fe, Mn and Zn in five shrub species that are consumed by small ruminants in the semi-arid regions of northeastern Mexico. Leaves samples of shrub species; Celtis pallida, Croton suaveolens, Forestiera angustifolia, Guaiacum angustifolium and Parkinsonia aculeata were randomly collected during twelve consecutive months from July 2018 to June 2019 in two sites, located in Linares and Los Ramones counties, in the state of Nuevo Leon, Mexico. Mineral content was analyzed using an atomic absorption spectrophotometer, while phosphorus was measured by the colorimetry method. The Linares county showed the highest content of macro- and micro-minerals. Among species, C. pallida showed the highest values of macrominerals and P. aculeata content of micro-minerals was highest. Ca (total mean = 40.0 g kg-1 DM), K (15.4 g kg-1), Mg (3.7 g kg-1), Fe (87.2 mg kg-1), Mn (35.5 mg kg-1) were available in adequate quantities, while P (1.3 g kg-1 DM), Cu (6.4 mg kg-1) and Zn (17.7 mg kg-1) were found deficient. Shrub species in this study can be considered as a good source of Ca, K, Mg, Fe and Mn except in C. suaveolens. However, P, Cu and Zn must be supplemented.